BAF60a Deficiency in Vascular Smooth Muscle Cells Prevents Abdominal Aortic Aneurysm by Reducing Inflammation and Extracellular Matrix Degradation. Issue 10 (October 2020) - Chang, Ziyi; Zhao, Guizhen; Zhao, Yang; Lu, Haocheng; Xiong, Wenhao; Liang, Wenying; Sun, Jinjian; Wang, Huilun; Zhu, Tianqing; Rom, Oren; Guo, Yanhong; Fan, Yanbo; et al.
Abstract : Objective: Currently, there are no approved drugs for abdominal aortic aneurysm (AAA) treatment, likely due to limited understanding of the primary molecular mechanisms underlying AAA development and progression. BAF60a—a unique subunit of the SWI/SNF (switch/sucrose nonfermentable) chromatin remodeling complex—is a novel regulator of metabolic homeostasis, yet little is known about its function in the vasculature and pathogenesis of AAA. In this study, we sought to investigate the role and underlying mechanisms of vascular smooth muscle cell (VSMC)–specific BAF60a in AAA formation. Approach and Results: BAF60a is upregulated in human and experimental murine AAA lesions. In vivo studies revealed that VSMC-specific knockout of BAF60a protected mice from both Ang II (angiotensin II)–induced and elastase-induced AAA formation with significant suppression of vascular inflammation, monocyte infiltration, and elastin fragmentation. Through RNA sequencing and pathway analysis, we found that the expression of inflammatory response genes in cultured human aortic smooth muscle cells was significantly downregulated by small interfering RNA–mediated BAF60a knockdown while upregulated upon adenovirus-mediated BAF60a overexpression. BAF60a regulates VSMC inflammation by recruiting BRG1 (Brahma-related gene-1)—a catalytic subunit of the SWI/SNF complex—to the promoter region of NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) target genes. Furthermore, loss of BAF60a in VSMCs prevented the upregulation of the proteolytic enzyme cysteine protease CTSS (cathepsin S), thus ameliorating ECM (extracellular matrix) degradation within the vascular wall in AAA. Conclusions: Our study demonstrated that BAF60a is required to recruit the SWI/SNF complex to facilitate the epigenetic regulation of VSMC inflammation, which may serve as a potential therapeutic target in preventing and treating AAA. Abstract : Supplemental Digital Content is available in the text.